One-Pot Synthesis of Metallopyrazinoporphyrazines Using 2, 3-Diaminomaleonitrile and 1, 2-Dicarbonyl Compounds Accelerated by Microwave Irradiation. (27th February 2014) - Maleki, Ali; Rezayan, Ali Hossein
Abstract : A one-pot microwave-assisted synthesis of metallopyrazinoporphyrazines as porphyrazine derivatives carrying six-membered pyrazine rings annulated at the periphery of the tetrapyrrolic macrocycle is described starting from 2, 3-diaminomaleonitrile, 1, 2-dicarbonyl compounds, metal salts, and urea.